Egg incubation temperature affects the timing of the Atlantic salmon Salmo salar homing migration. Issue 5 (31st October 2018) - Jonsson, Bror; Jonsson, Nina
Abstract : Here, we show that adult Atlantic salmon Salmo salar returned about 2 weeks later from the feeding areas in the North Atlantic Ocean to the Norwegian coast, through a phenotypically plastic mechanism, when they developed as embryos in c. 3°C warmer water than the regular incubation temperature. This finding has relevance to changes in migration timing caused by climate change and for cultivation and release of S. salar .